Near-Infrared Spectroscopy-Derived Dynamic Cerebral Autoregulation in Experimental Human Endotoxemia—An Exploratory Study - Eleveld, Nick; Hoedemaekers, Cornelia W. E.; van Kaam, C. Ruud; Leijte, Guus P.; van den Brule, Judith M. D.; Pickkers, Peter; Aries, Marcel J. H.; Maurits, Natasha M.; Elting, Jan Willem J. (Frontiers in Neurology, 2021)
Cerebral perfusion may be altered in sepsis patients. However, there are conflicting findings on cerebral autoregulation (CA) in healthy participants undergoing the experimental endotoxemia protocol, a proxy for systemic inflammation in sepsis. In the current study, a newly developed near-infrared spectroscopy (NIRS)-based CA-index is investigated in an endotoxemia study population, together with an index of focal cerebral oxygenation. Methods: Continuous-wave NIRS-data were obtained from eleven healthy participants receiving continuous infusion of bacterial endotoxin for 3 hours (Clinicaltrials.gov NCT02922673) under extensive physiological monitoring. Oxygenated-deoxygenated haemoglobin phase differences in the (very)low frequency (VLF/LF) bands and the Tissue Saturation Index (TSI) were calculated at baseline, during systemic inflammation, and at end-of-experiment 7 hours after initiation of endotoxin administration. Results: Median (IQR) LF-phase difference was 16.2 (3.0–52.6) degrees at baseline and decreased to 3.9 (2.0 – 8.8) degrees at systemic inflammation (p=0.03). LF-phase difference increased from systemic inflammation to 27.6 (12.7–67.5) degrees at end-of-experiment (p=0.005). No significant changes in VLF-phase difference were observed. TSI (mean±SD) increased from 63.7±3.4% at baseline to 66.5±2.8% during systemic inflammation (p=0.03) and remained higher at end-of-experiment (67.1±4.2%, p=0.04). Further analysis did not reveal a major influence of changes in several covariates such as blood pressure, heart rate, PaCO2 and temperature, although some degree of interaction could not be excluded Discussion: A reversible decrease in NIRS-derived cerebral autoregulation phase difference was seen after endotoxin infusion, with a small, sustained increase in TSI. These findings suggest that endotoxin administration in healthy participants reversibly impairs CA, accompanied by sustained microvascular vasodilation.